Cancer stem cell generation by silenced MAPK enhancing PI3K/AKT signaling. (August 2020) - Hassan, Ghmkin; Du, Juan; Afify, Said M.; Seno, Akimasa; Seno, Masaharu
Abstract: Cancer stem cells, which are defined by self-renewal, differentiation potential and tumorigenicity, are proposed to be responsible for cancer initiation and maintain the tumor mass. Cancer stem cells are thought to be resistant to chemotherapy inhibiting different signaling pathways. This might sound stemness is maintained even when the growth is suppressed. Typically, growth factors are known to stimulate MEK/ERK pathways, which is responsible for mitogenic activity, while the PI3K appears more related with the maintenance of stemness. The cross-talk, even in positive or negative ways, between these two pathways could stimulate or accelerate the conversion of normal stem cells into cancer stem cells. Here, we propose a new hypothesis of a mechanism for the conversion of stem cells or progenitors including induced pluripotent stem cells (iPSCs) to tissue-specific cancer stem cells. This conversion could be prepared by inhibiting MEK/ERK pathway and enhancing PI3K/AKT pathway exploiting conditioned media derived from cancer cell lines, which are good sources of many different cytokines, chemokines, tissues-specific factors, metabolites and so on, together with some inhibitors. The feasibility of this combination will be explained in this hypothesis through the reports published somewhere. Generation of cancer stem cells using embryonic stem cells/iPSCs will bring new theory in the mechanisms of tumorigenesis and assist drug screening that applies for the precision medicines for individuals.